Islamization of English literary studies - Hasan, Md. Mahmudul (2018)
The intellectual movement of looking at conventional knowledge systems in a critical manner and of incorporating Islamic values and perspectives into different fields of studies that (re-)surfaced with the establishment of the Association of Muslim Social Scientists (AMSS) in 1972 and the Washington, DC-based International Institute of IslamicThought (IIIT) in 1981 has huge potentials as an academic movement. However, it will be self-righteous on the part of the proponents and supporters of what is now widely known as the Islamization of Knowledge undertaking to say that they are the first to call into question western knowledge, as it will amount to de-recognizing other criticisms and contestations of modern education systems as essentially colonial discourse. Among others, two prominent academic communities have been vociferous against dominant educational practices that are deeply rooted in hegemonic discourses and disprivilege non-western knowledge systems and discourses.